Transcultural translation and validation of Fugl–Meyer assessment to Italian. Issue 25 (4th December 2021) - Cecchi, F.; Carrabba, C.; Bertolucci, F.; Castagnoli, C.; Falsini, C.; Gnetti, B.; Hochleitner, I.; Lucidi, G.; Martini, M.; Mosca, I. E.; Pancani, S.; Paperini, A.; et al.
Abstract: Purpose: The Fugl–Meyer Assessment is the most used and highly recommended clinical assessment of sensorimotor function after stroke. A standardized use of the scale in different countries requires translation and cultural validation to the target language. The objective of the study was to develop an official Italian version of the scale by transcultural translation and validation. Methods: A standardized multistep translation protocol was adopted to achieve optimal conceptual and semantic equivalence. The developed Italian version was validated in 10 post-stroke hemiparetic patients. Items with low intra- and interrater agreement, quantified as percentage of agreement <70% and/or statistically significant disagreement in relative position or concentration, between different raters were identified and revised. Results: All motor items received a high level of agreement with values well above 70%. Disagreements were observed in 6 items in the sensory, joint range and pain domains and 1 in one reflex item. Items showing disagreements were discussed and revised to establish the final Italian version. Conclusions: The culturally validated Italian Fugl–Meyer Assessment can reliably be used in research and in clinical practice. A standardized use will improve the quality of sensorimotor assessment in stroke across Italy and allow reliable comparisons of stroke populations internationally. Implications for rehabilitation: The Fugl–Meyer Assessment is the gold standard for evaluation of sensorimotor impairment after stroke. Having access to a transculturally validated official Italian version of Fugl–Meyer Assessment will improve the quality of sensorimotor assessment after stroke among Italian health professionals and researchers. A wider standardized use of the Fugl–Meyer Assessment in Italy will allow reliable international comparison of stroke rehabilitation outcomes.